2008
DOI: 10.1177/00333549081230s304
|View full text |Cite
|
Sign up to set email alerts
|

Patient Perceptions and Acceptance of Routine Emergency Department HIV Testing

Abstract: The Centers for Disease Control and Prevention's 2006 recommendations on HIV screening are well accepted by the target populations. Further work at explaining the risk of HIV infection to ED patients should be undertaken and may boost the acceptance rate of ED HIV screening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
58
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 79 publications
(66 citation statements)
references
References 7 publications
6
58
1
Order By: Relevance
“…Brown et al 28 also performed an HIV screening program based on the CDC recommendations for testing in health care settings, with an acceptance rate of HIV screening of 53%, which is not appreciably higher than the average acceptance (51%) of other routine screening programs using the opt-in methodology [13][14][15][16][17][18][19] and much lower than ours. Thus, in addition to the use of the opt-out approach, there are several other features of our program that seem to contribute to the higher acceptance rates.…”
Section: Discussionmentioning
confidence: 73%
See 4 more Smart Citations
“…Brown et al 28 also performed an HIV screening program based on the CDC recommendations for testing in health care settings, with an acceptance rate of HIV screening of 53%, which is not appreciably higher than the average acceptance (51%) of other routine screening programs using the opt-in methodology [13][14][15][16][17][18][19] and much lower than ours. Thus, in addition to the use of the opt-out approach, there are several other features of our program that seem to contribute to the higher acceptance rates.…”
Section: Discussionmentioning
confidence: 73%
“…Nonetheless, the acceptance rate in our program is much higher than that noted in most testing programs that have offered routine HIV screening. [13][14][15][16][17][18][19]28,30 Although many of these routine HIV screening programs demonstrated that over half of the patients tested will accept testing, most used screening models that required separate consent for HIV testing or for study participation and did not use the opt-out approach currently recommended by the CDC. Our findings illustrate that streamlining the consent and counseling procedures and the opt-out approach for HIV testing in health care settings may promote high test acceptance in the ED.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations